Pengaruh Kepercayaan, Pengetahuan, Dan Aksesibilitas Terhadap Keputusan Muzakki Dalam Menggunakan Digital Payment (Studi Kasus Muzakki Kota Medan) - Ritonga, Lilis Suryani; Anggraini, Tuti; Yanti, Nursantri (Universitas Labuhanbatu, 2024)
The purpose of this study is to determine the effect of trust, knowledge, and accessibility to the decision muzakki in using digital payment for zakat payments. This study uses a quantitative approach. Data collection using a questionnaire with a purposive sampling of 80 respondents. The test results simultaneously showed that trust, knowledge, and accessibility influenced muzakki's decision to use digital payment with a sign value of 0.000 < 0.05. The test results through multiple linear regression analysis test showed that confidence significantly affect the decision muzakki using digital payment with a value of 0.18 < 0.05. The test results through multiple linear regression analysis test found that knowledge significantly affect the decision muzakki using digital payment with a value of 0.005 < 0.05. The test results through multiple linear regression analysis test found that accessibility significantly affect the decision muzakki using digital payment with a value of 0.000 < 0.05.